Protection Motivation Theory and Rabies Protective Behaviors Among School Students in Chonburi Province, Thailand - Mayurin Laorujisawat; Aimutcha Wattanaburanon; Pajaree Abdullakasim; Nipa Maharachpong (Korean Society for Preventive Medicine, 2021)
Objectives The aim of this study was to predict rabies protective behaviors (RPB) based on protection motivation theory (PMT) among fourth-grade students at schools in Chonburi Province, Thailand. Methods This cross-sectional study was conducted from December 2020 to February 2021. A multistage sampling technique was used for sample selection. The questionnaire was divided into socio-demographic data and questions related to PMT and RPB. Descriptive statistical analysis was conducted using the EpiData program and inferential statistics, and the results were tested using the partial least squares model with a significance level of less than 5%. Results In total, 287 subjects were included, of whom 62.4% were girls and 40.4% reported that YouTube was their favorite media platform. Most participants had good perceived vulnerability, response efficacy, and self efficacy levels related to rabies (43.9, 68.6, and 73.2%, respectively). However, 54.5% had only fair perceived severity levels related to rabies. Significant positive correlations were found between RPB and the PMT constructs related to rabies (β, 0.298; p<0.001), and the school variable (S4) was also a predictor of RPB (β, -0.228; p<0.001). Among the PMT constructs, self efficacy was the strongest predictor of RPB (β, 0.741; p<0.001). Conclusions PMT is a useful framework for predicting RPB. Future RPB or prevention/protection intervention studies based on PMT should focus on improving self efficacy and response efficacy, with a particular focus on teaching students not to intervene with fighting animals. The most influential PMT constructs can be used for designing tools and implementing and evaluating future educational interventions to prevent rabies in children.